2008
DOI: 10.1007/s10811-008-9389-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three gracilarioids: growth rate, agar content and quality

Abstract: Three gracilarioid species, Gracilariopsis bailiniae and Gracilaria tenuistipitata from Vietnam and Gracilaria gracilis from Russia, were studied in order to determine whether Gracilaria gracilis might be a superior species for cultivation in brackish-water ponds for agar production compared with the Vietnamese species. The effects of different salinity levels on the growth rate and agar production as well as agar properties of three gracilarioid species were compared in controlled laboratory experiments. Grac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
1
13
0
1
Order By: Relevance
“…without re-extraction steps (e.g. Arvizu-Higuera et al, 2008;Lewis & Hanisak, 1996;Skriptsova & Nabivailo, 2009;Villanueva et al, 2010). Nevertheless, extraction yields below 10% were reported for G. tikvahiae (Lopezbautista & Kapraun, 1995), making the yields achieved in this work significant.…”
Section: Yield Gel Strength and Physico-chemical Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…without re-extraction steps (e.g. Arvizu-Higuera et al, 2008;Lewis & Hanisak, 1996;Skriptsova & Nabivailo, 2009;Villanueva et al, 2010). Nevertheless, extraction yields below 10% were reported for G. tikvahiae (Lopezbautista & Kapraun, 1995), making the yields achieved in this work significant.…”
Section: Yield Gel Strength and Physico-chemical Propertiesmentioning
confidence: 85%
“…Gelling temperatures were slightly higher than the typical gelling temperatures of commercial agars, which are generally below 40°C, but common in agar from Gracilaria sp., particularly if highly methylated. Despite the good gelling ability, the gel temperatures above 32-36°C made these agars unsuitable for direct use in bacteriological grade applications (Skriptsova & Nabivailo, 2009).…”
Section: Yield Gel Strength and Physico-chemical Propertiesmentioning
confidence: 99%
“…to abiotic factors such as light intensity, pH, salinity, temperature [22,23]. This showed that environmental parameters play essential role in the growth and carrageenan contain.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics together with a high growth rate and high agar yield make this strain suitable for cultivation, and it has been extensively cultivated in ponds in Southern China and Taiwan (Chiang 1981). G. tenuistipitata has also been increasingly used as a model species in studies on red algal physiology (Carnicas et al 1999;Collén et al 2003;Falcão et al 2008Falcão et al , 2010García-Sánchez et al 1994;Pedersén 1992, 1993;Haglund et al 1996;Hu et al 1996;Lopes et al 1997Lopes et al , 2002Mercado et al 2001;Nyvall et al 1999;Nyvall Collén et al 2004;Skriptsova and Nabivailo 2009;Xu et al 2009;Yokoya et al 2004;Yu and Pedersén 1993). Another example of the growing interest in this alga is the sequencing of its chloroplast (Hagopian et al 2004) and mitochondrial (Takahashi 2010) genomes as well as completion of its life history in the laboratory (Barufi et al 2010).…”
Section: Introductionmentioning
confidence: 99%